Recombinase Amplification Method Applied to Meat and Halal Authentication: Trends and Potential Implications - Siti Nurul Bazilah Haji Mohaimin; Moohamad Ropaning Sulong; Nur Thaqifah Salihah Haji Mohd Salleh (Universiti Sains Islam Malaysia, 2026)
The rapid evolution of technology and the food industry has raised concerns about the accurate labelling of Halal food and meat authentication. The Halal authentication system maintains a zero-tolerance policy regarding the halal status of food products from farm to fork. As a result, innovative technologies such as recombinase polymerase amplification are necessary to address the growing issues of food fraud and enhance the current species identification method. Recombinase amplification method is an isothermal amplification process that operates at 37-42°C without the need for specialized equipment or technicians. A systematic review was conducted to analyse research on the application of Recombinase Amplification method in meat and Halal authentication, covering literature published from 2018 to 2024. Relevant studies were identified through a comprehensive search of established databases in which 25 studies met the inclusion criteria, focusing specifically on meat and Halal authentication, while studies related to clinical diagnostics and microbiological testing were excluded. This paper aims to analyse the various detection technologies integrated with Recombinase Polymerase Amplification (RPA) and to provide a comprehensive review of the application of RPA in meat and Halal authentication. The review will summarise current trends and evaluate the potential future developments and implications of RPA-based methods for establishing a reliable and rapid on-site auditing system.